(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2018)
The prompt response to emergency situations involving suspicion of intakes of radionuclides requires the use of simple and rapid methods of internal monitoring of the exposed individuals. The use of gamma cameras to estimate intakes and committed doses was investigated by the Centers for Disease Control and Preventions (CDC) of the USA in 2010.The present study aims to develop a calibration protocol for gamma cameras to be applied on internal monitoring based on urine samples to evaluate the incorporation of high-energy photon emitting radionuclides in emergency situations. A gamma camera available in a public hospital located in the city of Rio de Janeiro was calibrated using a standard liquid source of 152Eu supplied by the LNMRI of the IRD. “Efficiency vs Energy” curves at 2 and 10 cm were obtained. Calibration factors, Minimum Detectable Activities and Minimum Detectable Effective Doses of the gamma camera were calculated for 131I and 137Cs. The gamma camera evaluated in this work presents enough sensitivity to detect activities of such radionuclides at dose levels suitable to assess suspected accidental intakes.